Sto lat na Nowym Swiecie - Budrewicz, Olgierd; Topolski, Feliks, 1907-1989.; Blikle family (Warszawa : Sport i Turystyka, 1969)
The history of the famous Varsovian cafe and bakery, owned by the Blikle family, as remembered by various people.
One folded leaf in pocket.
Keywords: Streets -- Poland; Ulica Nowy Swiat (Warsaw, Poland)